Effect of feeding carrot flour on performance and profitability of broilers - Jácome Gómez, Janeth; Loor Moreira, Gina; De la Cruz Chicaiza, Marco; Intriago Vera, Janeth; Espinoza Zambrano, Jeniffer; Zambrano Rivera, Milton (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: The quality of chicken meat, essential for consumer satisfaction, is influenced by skin pigmentation. The lack of carotenoids in conventional diets has driven the search for costeffective alternatives to enhance these aspects in poultry production. Objective: This study assessed the impact of partially replacing commercial balanced feed with different levels of carrot flour (Daucus carota subsp. sativus) on productive parameters and the pigmentation of broiler chickens. Methods: Sixty-four Cobb 500 birds were randomly assigned to four experimental diets, each with eight replicates of two birds. The control group (T0) received a standard diet, while the experimental groups received a diet with 10% (T1), 15% (T2), and 20% (T3) replacement with carrot flour (CF). Variables such as feed consumption, weight gain, feed conversion, mortality, skin pigmentation, and profitability were evaluated. Results: Treatments with 15% and 20% CF resulted in significantly higher feed consumption (p < 0.05) compared to the control group. Although weight gain did not show significant differences between groups (p > 0.05), a trend towards higher gains was observed in the experimental groups. The feed conversion ratio increased non-significantly (p > 0.05) with higher CF concentrations. No mortality was observed in the experimental groups, whereas the control group had a mortality rate of 12.5%. Regarding pigmentation, CF influenced skin color as its concentration in the diet increased. In terms of profitability, the 15% replacement treatment stood out by generating higher income and a superior cost-benefit ratio. Conclusion: Orange cultivar CF can be a viable dietary source of natural pigment for broiler chickens. It may also be beneficial in promoting weight gain and reducing mortality, translating into economic advantages.